2020
DOI: 10.1007/s13197-020-04462-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of active Kurdi gum and Farsi gum-based coatings in banana fruits

Abstract: This study evaluated the effects of Kurdi gum (KG) and Farsi gum (FG) based coatings with and without ethanolic Prosopis farcta extract (PFE; 0, 0.25 and 0.5%) on microbial, physicochemical, and sensory properties as well as respiration and ethylene production rates of banana fruits during storage (13 °C, 80% relative humidity (RH)) for 21 days and afterward 7 days at simulated market conditions (25 °C, 60% RH). The treatment of fruits with KG ? PFE 0.5% resulted in the best bacterial, chemical, and sensory pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…After 6 days of storage, bananas with coating had higher firmness quality than uncoated ones. The coating provided a physical barrier, which can inhibit the respiration and evaporation of the peel, thus delaying the ripening of the fruit . In addition, 0.50% CDs/PVA sample had significantly higher ( p < 0.05) firmness as compared to the PVA sample, demonstrating that the 0.50% CDs/PVA film was better than the PVA film in delaying banana maturation, which may be due to its high water resistance property and excellent antioxidant performance.…”
Section: Resultsmentioning
confidence: 98%
“…After 6 days of storage, bananas with coating had higher firmness quality than uncoated ones. The coating provided a physical barrier, which can inhibit the respiration and evaporation of the peel, thus delaying the ripening of the fruit . In addition, 0.50% CDs/PVA sample had significantly higher ( p < 0.05) firmness as compared to the PVA sample, demonstrating that the 0.50% CDs/PVA film was better than the PVA film in delaying banana maturation, which may be due to its high water resistance property and excellent antioxidant performance.…”
Section: Resultsmentioning
confidence: 98%
“…The total plate count of the palmyra sap samples was measured using the plate count agar method given by Shahbazi and Shavisi (2020). An aliquot (100 μl) of the sample after serial dilution was aseptically inoculated in pre‐sterilized plates with plate count agar after solidification under the sterile environment of laminar airflow.…”
Section: Methodsmentioning
confidence: 99%
“…The total plate count of the palmyra sap samples was measured using the plate count agar method given by Shahbazi and Shavisi (2020).…”
Section: Total Plate Countmentioning
confidence: 99%
“…Calcium impedes the softening by chelating with the pectin, also, the coating of chitosan with calcium propionate increases the firmness of the slices by 2.3 times (Mirshekari et al., 2017). Recently, a study concluded that a gum based coating provided a shelf life of 21 days at 13 °C (Shahbazi & Shavisi, 2020).…”
Section: Pre‐processed Fruits and Their Process Conditionsmentioning
confidence: 99%